The effects of design decisions on service life and life cycle cost for a concrete slab in a parking garage - Badr, Ali, author; Atadero, Rebecca, advisor; Jia, Gaofeng, committee member; Valdes-Vasquez, Rodolfo, committee member (Colorado State University. Libraries, 2017)
Parking garages are unique structures that are useful and common as part of the transportation infrastructure system in the US. Large percentage of these structures is open which expose them to ambient environment and in some cases deleterious chloride exposures. Corrosion of embedded steel is the main cause for concrete deterioration and chloride exposure is one of the major causes for corrosion. Therefore, designing these structures for durability is essential to extend their service life and reduce their degradation status and future repair costs. Improving the durability of these structures can be a costly process at the construction phase that might leave owners of parking garages reluctant about increasing the upfront costs. Therefore, Life-365 software has been used in this study to investigate the service life and life cycle cost impacts of different design decisions throughout the lifetime on a reinforced concrete slab element in a parking garage. Life Cycle Cost Analysis "LCCA" is a process that weights the trade-offs of different phases cost including initial construction and subsequent maintenance and repair throughout the design life period and can help understand the long-term value of additional upfront costs. In Life-365, service life is the sum of two periods: the initiation period and the propagation period while LCC is the sum of three cost phases :the construction phase, the barrier phase and the repair phase which starts at the end of the service life period and extends the remainder of design life. The design decisions or design variables that are investigated in this study include varying the concrete cover distance to the embedded steel, varying the w/cm ratio, using different supplementary cementitious materials, using different barriers and reinforcement types. The geographic location of the parking garage was chosen as Denver, Colorado. Corrosion is likely to occur in this city where harsh environmental conditions are present, including snow falling into parking garages' decks or using deicing salts to melt accumulated snow on roads which can be carried by tires or underneath automobiles. Results of this study showed that using supplementary cementitious materials are the best design variables to consider in terms of saving money for the concrete slab during its design life, besides increasing the concrete cover distance. In addition, a combination of SCMs with a low w/cm ratio has proven to be very effective in terms of reducing costs especially when it is used with higher concrete cover. This study can help designers and owners of these structures in managing and allocating the resources they have more effectively.
Keywords: life cycle cost analysis; durability; parking garages